Existence of Center for Planar Differential Systems with Impulsive Perturbations. (5th May 2015) - Xu, Dengguo
Abstract : We present a method that uses successor functions in ordinary differential systems to address the "center-focus" problem of a class of planar systems that have an impulsive perturbation. By deriving solution formulae for impulsive systems, several interesting criteria for distinguishing between the center and the focus of linear and nonlinear planar systems with state-dependent impulsions are established. The conditions describing the stability of the focus of the considered models are also given. The computing methods presented here are more convenient for determining the center of impulsive systems than those in the literature. Numerical examples are given to show the effectiveness of the theoretical results.